Evaluation of novel multimedia education to train doctors to discuss advance care planning (ACP). Issue 2 (1st June 2012) - Detering, K; Renton, J; Corke, C; Milne, S; Silvester, W
Abstract : Despite evidence of significant benefits of ACP for patients and relatives, many doctors lack the confidence to have ACP discussions with patients. To improve the ability of doctors to undertake these conversations, the "Next Steps" program – funded by the Victorian Quality Council - was developed, comprising an E-simulation, DVD, interactive workshop and reading materials. Initial evaluation entailed participants completing surveys pre and post training. Data includes demographics, 8 questions on ACP knowledge, 10 questions on attitudes to ACP, 8 questions regarding confidence to discuss ACP and an E-simulation score (maximum score 80). Participants also rated all educational tools. 148 doctors attended the workshop (51% Male, 72% <41 years old, 62% trained overseas), attended the workshop, 46% completed both pre and post questionnaires, and 45% did the e-simulation. Knowledge levels were high pre training and improved significantly (mean pre 5.9/8, post 6.7 p <0.05). There was an overall trend to a change in attitude, but only 2 questions had a statistically significant change. There was a statistically significant improvement in the level of confidence on 6 questions. The E-simulation score increased significantly (pre 18, post 53.5, p < 0.005). Most participants rated the materials highly, rated the interactive workshop the highest, and preferred the use of a combination of materials. "Next Steps" was well received and improved knowledge, attitudes, and confidence to discuss ACP amongst a small group of doctors. This training will facilitate doctors developing the skills and confidence to provide ACP.